(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
“Diabetes Diagnosis” contains safe and useful information for patients with diabetes. Patients diagnosed with diabetes can read the resources listed in this article and get the advice they need. It also provides information the influential factors that can cause or be effecting to diabet, once a reader gets a full information about it, he should avoid this affects. Moreover, there is information about types of diabetes and the way they lead to a severe health problem. To avoid all of these I also illustrate some key factors to avoid immediately, as they are harmful and performances that should be taken.